2010
DOI: 10.1016/j.neuron.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Fear Thou Not: Activity of Frontal and Temporal Circuits in Moments of Real-Life Courage

Abstract: How does the brain encode courage in a real-life fearful situation that demands an immediate response? In this study, volunteers who fear snakes had to bring a live snake into close proximity with their heads while their brains were scanned using functional magnetic resonance imaging (fMRI). Bringing the snake closer was associated with a dissociation between subjective fear and somatic arousal. Activity in the subgenual anterior cingulate cortex (sgACC) and the right temporal pole was positively correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 52 publications
(66 reference statements)
8
58
0
Order By: Relevance
“…The data suggest that this behavior may be related to trying to find a method to escape the operant shock chamber. This is consistent with a recent human imaging study (Nili et al, 2010), which shows that the ACC may be involved in overcoming fear (i.e., courage). Since we do not give the mouse an opportunity to escape the operant chamber, the animal may only execute a small part of an escape motor plan (e.g., a lifting of the head or movements to inspect the confines of the operant chamber).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The data suggest that this behavior may be related to trying to find a method to escape the operant shock chamber. This is consistent with a recent human imaging study (Nili et al, 2010), which shows that the ACC may be involved in overcoming fear (i.e., courage). Since we do not give the mouse an opportunity to escape the operant chamber, the animal may only execute a small part of an escape motor plan (e.g., a lifting of the head or movements to inspect the confines of the operant chamber).…”
Section: Discussionsupporting
confidence: 93%
“…The seemingly multimodal behavior of neurons, overlapping with motor movements and pain, makes sense if an animal is to avoid pain in the future through motor behavior, and fits nicely with recent predictions for the overlap of pain and movement systems (Dum et al, 2009) and the involvement of the ACC in courageous behavior (Nili et al, 2010). However, it is surprising that ACC neuron activity would correlate with motor behavior even when the animal is not experiencing pain (i.e., during the trace fear interval).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, we indeed observed that vmPFC (subgenual anterior cingulate) was involved in the development of blocking, but its responseswhich were characterized by a significant deactivation-were limited to the comparison of CSAX versus CSA. This selective response is especially interesting given this region's involvement in the control of conditioned fear in animals (Rosenkranz et al, 2003;Vidal-Gonzalez et al, 2006) and in both automatic and voluntary forms of fear regulation in humans (Phelps et al, 2004;Delgado et al, 2008a;Klumpers et al, 2010;Nili et al, 2010), but obviously it leaves open the question via which pathway the dlPFC-mediated upregulation of amygdala responses-as observed on BY trials-is realized.…”
Section: Discussionmentioning
confidence: 99%
“…Correction for multiple comparisons using Gaussian random field theory was based on probabilistic maps of our target regions (obtained from the Harvard-Oxford atlas and thresholded at 50%): amygdala, dlPFC (approximated by the middle frontal gyrus mask), and ventromedial PFC (vmPFC)/subgenual anterior cingulate cortex (sgACC) (approximated by the subcallosal cortex mask, which is somewhat overly conservative as it also includes more lateral parts). While the terminology used to describe this latter region is rather inconsistent across studies, note that we were specifically interested in the subgenual anterior cingulate cortex, as it shows a very prominent involvement in various processes of human fear control (Phelps et al, 2004;Delgado et al, 2008a;Klumpers et al, 2010;Nili et al, 2010). No probabilistic maps exist for dACC and AI, which we therefore approximated by spheres (10 mm radius) centered on coordinates from a recent meta-analysis of fear conditioning (Mechias et al, 2010).…”
Section: Methodsmentioning
confidence: 99%